Contribution of strength characteristics to change of direction and agility performance in female basketball athletes - Spiteri, T.; Nimphius, S.; Hart, N. H.; Specos, C.; Sheppard, J. M.; Newton, R. U. (The Journal of Strength and Conditioning Research, 2014)
Research has often examined the relationship between 1 or 2 measures of strength and change of direction (COD) ability reporting inconsistent relationships to performance. These inconsistencies may be the result of the strength assessment used and the assumption that 1 measure of strength can represent all "types" of strength required during a COD task. Therefore the purpose of this study was to determine the relationship between several lower-body strength and power measures, COD, and agility performance. Twelve (n = 12) elite female basketball athletes completed a maximal dynamic back squat, isometric midthigh pull, eccentric and concentric only back squat, and a countermovement jump, followed by 2 COD tests (505 and T-test) and a reactive agility test. Pearson product-moment correlation and stepwise regression analysis were performed on all variables. The percentage contribution of each strength measure to an athletes total strength score was also determined. Our results demonstrated that both COD tests were significantly correlated to maximal dynamic, isometric, concentric, and eccentric strength (r = -0.79 to -0.89), with eccentric strength identified as the sole predictor of COD performance. Agility performance did not correlate with any measure of strength (r = -0.08 to -0.36), whereas lower-body power demonstrated no correlation to either agility or COD performance (r = -0.19 to -0.46). These findings demonstrate the importance of multiple strength components for COD ability, highlighting eccentric strength as a deterministic factor of COD performance. Coaches should aim to develop a well-rounded strength base in athletes; ensuring eccentric strength is developed as effectively as the often-emphasized concentric or overall dynamic strength capacity.